2003
DOI: 10.1046/j.1523-1747.2003.12146.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potential Effector Function for IgE Autoantibodies in the Organ-Specific Autoimmune Disease Bullous Pemphigoid

Abstract: Bullous pemphigoid (BP) is an autoimmune skin disease characterized by autoantibodies against the hemidesmosomal protein BP180. In addition to IgG autoantibodies, IgE class autoantibodies have been reported in BP patients. Because animal models utilizing only IgG antibodies do not totally replicate human BP, we examined the specificity and potential relevance of IgE autoantibodies in this disease. Thirty BP patients participated in these studies. Serum IgE was measured and the IgE specificity was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
2
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 32 publications
(28 reference statements)
9
124
2
9
Order By: Relevance
“…These processes are probably a reflection of their "physiological" role in the control of parasitic infections, which can also be associated with higher IgE levels, an activated mast cell phenotype, and the persistent presence of antigen. A role for antigen-specific IgE in autoimmunity has previously been demonstrated (14,15). Bullous pemphigoid (BP) is an autoimmune skin disease characterized by subepidermal blistering.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are probably a reflection of their "physiological" role in the control of parasitic infections, which can also be associated with higher IgE levels, an activated mast cell phenotype, and the persistent presence of antigen. A role for antigen-specific IgE in autoimmunity has previously been demonstrated (14,15). Bullous pemphigoid (BP) is an autoimmune skin disease characterized by subepidermal blistering.…”
Section: Discussionmentioning
confidence: 99%
“…40 In clinical terms, total IgE levels are elevated in 70% of untreated BP patients and IgE autoantibodies against COL17 are detected in 86% of untreated BP patients. 41 Iwata et al 42 reported that the presence of IgE autoantibodies against COL17 was associated with a severe form of BP, and BP patients with IgE anti-COL17 antibodies required a longer period of treatment for remission, a higher dose of prednisolone, and more intensive treatments for remission. These findings suggest that IgE autoantibodies against COL17 are associated with BP pathogenesis and disease activity.…”
Section: Ige Autoantibodies In Bpmentioning
confidence: 99%
“…İnsan monoklonal anti-IgE otoantikoru olan omalizumab (OMZ), immün hücreler üzerinde IgE ekspresyonunu azaltarak ve IgE'nin reseptörüne bağlanmasını önleyerek mast hücreleri ve bazofiller üzerinde IgE etkisini nötralize etmiş olur 13,14 . Tedavi edilmemiş BP hastalarının çoğunda artmış dolaşan IgE seviyesi ve aynı ekstrasellüler non-kollajenöz 16A (NC16A) bölgesini esas olarak hedef alan IgE otoantikorları gösterilmiştir [15][16][17] . Geçtiğimiz yıllarda BP patomekanizmasındaki IgE'nin kritik rolünü ortaya koyan deneysel çalışmalara göre, IgE/IgE reseptör etkileşiminin inhibisyonu hastalığın tedavisinde umut verici bir tedavi seçeneği olmuştur [18][19][20][21] .…”
Section: Introductionunclassified